2021
DOI: 10.1108/pijpsm-02-2021-0034
|View full text |Cite
|
Sign up to set email alerts
|

Examining police officers’ perceptions of stress: the role of Person−environment fit

Abstract: PurposeThe purpose of the study was to examine the relationship between officer perceptions of fit in their organization and stress (organizational and operational), overall job satisfaction and turnover contemplation (within the last 6 months).Design/methodology/approachThe authors used cross-sectional survey data from a sample of 832 officers from two Midwest police departments to examine the relationships between fit, stress and work-related attitudes.FindingsPerceived stress and organizational fit were str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 64 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…Previous research has shown that cortisol levels are in uenced by individual personality characteristics [48,49] and physical health [50,51], which helps explain the relationship between CF and hair cortisol concentration. Additionally, previous studies have demonstrated a negative correlation between t levels and burnout [52] and turnover contemplation [53], and a positive correlation with job satisfaction [54]. Burnout [55] and satisfaction[56] are signi cant in uencing factors for the uctuate of cortisol in occupational population.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that cortisol levels are in uenced by individual personality characteristics [48,49] and physical health [50,51], which helps explain the relationship between CF and hair cortisol concentration. Additionally, previous studies have demonstrated a negative correlation between t levels and burnout [52] and turnover contemplation [53], and a positive correlation with job satisfaction [54]. Burnout [55] and satisfaction[56] are signi cant in uencing factors for the uctuate of cortisol in occupational population.…”
Section: Discussionmentioning
confidence: 99%
“…, 2022; Noblet et al. , 2009; Paoline and Gau, 2020; Rief and Clinkinbeard, 2021; Shane, 2010). The impact of occupational stress extends beyond that of poor police performance and unfavorable orientations toward the job, as heightened stress can result in a variety of home troubles (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Extant literature has noted the far-reaching consequences of work-based stress among police officers. A number of on-the-job deficiencies have been identified as a result of occupational stress including, but not limited to, accidents, citizen complaints, calling in sick, absenteeism, decreased organizational commitment, job dissatisfaction, cynicism, burnout and turnover intentions (Burke and Deszca, 1986;Ivie and Garland, 2011;Jermier et al, 1989;Lambert et al, 2022;Noblet et al, 2009;Paoline and Gau, 2020;Rief and Clinkinbeard, 2021;Shane, 2010). The impact of occupational stress extends beyond that of poor police performance and unfavorable orientations toward the job, as heightened stress can result in a variety of home troubles (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This theory states that stress of the employees are the result of his or her interaction with the environment. Rief and Clinkinbeard (2021) stated that according to the PE theory the stress of the employee of an organization is determined by the environment of that organization. According to Snyder et al (2018), in PE theory, stress occurs when the employee finds out the difference between their perception about the work environment and the actual environment (Edwards et al, 1998).…”
Section: Organizationalmentioning
confidence: 99%